Estimating the charge size in explosive forming of sheet metal - Noble, C. F. (College of Aeronautics, 1964)
A method is given for estimating the charge size for the explosive forming of sheet metal components. The method is applied to a number of relatively simple shapes and good agreement is shown with experimental results.